2022
DOI: 10.1099/ijsem.0.005232
|View full text |Cite
|
Sign up to set email alerts
|

Noviherbaspirillum aridicola sp. nov., isolated from an arid soil in Pakistan

Abstract: Strain NCCP-691T was isolated from a soil sample collected from an arid soil in Karak, Khyber Pakhtunkhwa, Pakistan. Phenotypically, the cells were Gram-stain-negative, aerobic and motile rods. The organism was able to grow between 20–40 °C (optimum at 30–37 °C), at pH 5.5–8.0 (optimum at pH 7.0–7.2) and tolerated 0–1.5% NaCl (w/v) (optimum at 0–0.5). Based on 16S rRNA gene sequences, strain NCCP-691T formed a distinct phylogenetic clade with Noviherbaspirillum ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(103 reference statements)
1
3
0
Order By: Relevance
“…The predominant cellular fatty acids of I16B-00201 T were identified as summed feature 3, summed feature 8 and C 12 : 0 (Table 2). Our experimental results, consistent with previous studies, demonstrated that summed feature 3 and summed feature 8 were the predominant fatty acids across all species, with C 16 : 0 also constituting a significant proportion in most species [1][2][3][4][5][6][7][8][9]. Although Lin et al reported saturated (C 12 : 0 , C 16 : 0 , and C 17 : 0 cyclo) and hydroxy (C 10 : 0 3-OH, C 14 : 0 2-OH, and iso-C 15 : 0 3-OH) fatty acids as major components [1], the significant variations and absence in some species suggested they were not ubiquitous across all species.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…The predominant cellular fatty acids of I16B-00201 T were identified as summed feature 3, summed feature 8 and C 12 : 0 (Table 2). Our experimental results, consistent with previous studies, demonstrated that summed feature 3 and summed feature 8 were the predominant fatty acids across all species, with C 16 : 0 also constituting a significant proportion in most species [1][2][3][4][5][6][7][8][9]. Although Lin et al reported saturated (C 12 : 0 , C 16 : 0 , and C 17 : 0 cyclo) and hydroxy (C 10 : 0 3-OH, C 14 : 0 2-OH, and iso-C 15 : 0 3-OH) fatty acids as major components [1], the significant variations and absence in some species suggested they were not ubiquitous across all species.…”
supporting
confidence: 93%
“…The polar lipid profile includes diphosphatidylglycerol (DPG), phosphatidylglycerol (PG), phosphatidylethanolamine (PE), and phosphatidylcholine (PC) [1]. The G+C content ranges from 59.7 to 65.5 mol% [1][2][3][4][5][6][7][8][9]. In this study, we present the taxonomic characterization of strain I16B-00201 T , a novel member of the genus Noviherbaspirillum, isolated from a particulate-polluted air sample in Beijing, China.…”
mentioning
confidence: 99%
See 2 more Smart Citations